Photostimulation of japanese quail - Molino, A. B. [UNESP] (2015)
To adapt commercial poultry production to a new scenario of energy savings and to develop specific practices for quail production aimed at reducing costs while maintaining or improving productivity, four experiments were conducted. In the first experiment, birds were allocated to four treatments (photoperiod duration): T1: 14L:10D; T2: 15L:9D; T3: 16L:8D; and T4: 17L:7D. In the second experiment, birds were subjected to four levels of brightness: T1: 5 lux; T2: 10 lux; T3: 15 lux; and T4: 22 lux (control). In the third experiment, four types of lamps were evaluated: T1: compact fluorescent lamp (color temperature: 6,500K); T2: compact fluorescent lamp (color temperature: 2,700K); T3: incandescent lamp; and T4: yellow LED. In the last experiment, four lighting programs were compared: T1: continuous program (control), in which there was a single photoperiod of 15 h; the other treatments consisted of intermittent lighting programs, as follows: T2: 1 h of light provided 1 h after dusk; T3: 1 h of light provided 2 h before dawn; T4: half an hour of light provided 1 h after dusk and half an hour of light provided 1.5 h before dawn. In each experiment, 1,296 Japanese quail were evaluated for four 28-d cycles, totaling 112 experimental days. A completely randomized experimental design of 4 treatments with 12 replicates of 27 birds each was applied in all trials. Performance and egg quality were evaluated in each experiment. Higher egg production and adequate egg quality, as well as energy savings, can be obtained with Japanese quail using compact fluorescent lamps or LEDs and a photoperiod of 15 h/d supplied using an intermittent lighting program, with 1 h of artificial light 2 h before dawn at a brightness of 5 lux.